Pierre Gilles' Constantinople : a Modern English Translation. - Gilles, Pierre (Historical Travel Ser., 2008)
This complete English edition of Pierre Gilles' Topography of Constantinople and Its Antiquities in Four Books is a study and history of the monuments of the former Byzantine capital, the largest and wealthiest city in Europe. It includes references to Gilles' sources and to the most important recent scholarship on the city and its monuments. This fine edition supplants John Ball's 1729 translation and its modernization published by Italica Press in 1988. It offers an important addition to the scholarship on Constantinople, its ancient heritage, and to the evolving study and practice of classi.